Hubungan Kekuatan Otot Lengan dan Berat Badan Terhadap Ketepatan Smash dalam Bola Voli di PBV. Pelopor Muda - Maulana, Abdillah; Basri, Mohammad Hasan; Suparto, Achmad (Jurnal Keolahragaan, 2025)
This study explores the significant relationship between arm muscle strength and body weight on smash accuracy in young volleyball athletes at PBV. Pelopor Muda, aged 15-16 years. Using correlational research design and descriptive statistical analysis as well as Pearson correlation, this study involved twelve athletes as a sample. The results showed that arm muscle strength contributed 52.2% to smash accuracy, while body weight showed a negative correlation of -0.700, which accounted for 49% of the variation in smash accuracy. These findings emphasize the importance of muscle strength in producing effective and accurate attacks, which can affect the outcome of a match. In addition, maintaining an ideal body weight is important to help athletes achieve better balance and stability during the game. This study emphasizes that muscle strength and weight management should be a focus in training programs to optimize athlete performance. Further discussion in this document links previous literature linking physical attributes to performance in volleyball, thus reinforcing the importance of structured training and athletic development in young populations. Further research is recommended to explore the interaction of other factors that influence performance, including overall physical fitness and nutritional strategies, in order to achieve a holistic training approach. The conclusion of this study emphasizes that muscle strength and body weight are important factors that directly affect the accuracy of volleyball smashes, and training interventions tailored to these attributes can improve the technical execution of volleyball skills